Makassar Copra as a Trigger of Struggling for Power between Central and Local Government: A Historical Study of Regional Political Economy in Indonesia - Asba, Abdul Rasyid (ASPENSI in Bandung, Indonesia, 2015)
ABSTRACT: Copra, as an economic commodity, was used as a political issue rather than overcoming economic problems. The concept of political self-reliance and anti-imperialism by means of nationalization on foreign companies in Indonesia, in 1950s, seem to be correlated directly with the discontinuity of Indonesian economy up to now. As an archipelago state, today Indonesia is threatened economic disintegration in the whole islands which gradually also threatens national disintegration. National integration can only be strengthened if it is followed by economic integration of all islands. National integration developed so far hasnât taken the maximum advantages of inter-island relation as an economic power, so that the economic policy of Indonesia seems to be partial. Consequently, the conflict between central and local government has always been highlighted by political aspects. The importance of economic power in supporting national integration wasÂ still kept freshly in mind of the whole community members of East Indonesia, since commodity of copra was placed as regional economic power in East Indonesia and being a national economy. However, when the politics dominantly controlled economic policy, the copra export trade system in the area collapsed. This situation was used by military in Sulawesi for controlling the copra export. They established new trade system namely barter system. As the result, economic integration was stagnant and monopolized by national political elite in Jakarta. Today, this regions (East Indonesia Â generally and South Sulawesi particularly) are only fragments of archipelagoâs economy for the sake of parties controlled by Jakarta. KEY WORDS: Economic commodity, copra, economic policy, central and local government, Sulawesi and East Indonesia region, and national integration and disintegration.About the Author: Prof. Dr. Abdul Rasyid Asba is a Lecturer at the Department of History, Faculty of Humanities UNHAS (Hasanuddin University), Jalan Perintis Kemerdekaan Km.10 Makassar, South Sulawesi, Indonesia; and also as a Director of Center for Multicultural and Regional Development at UNHAS Makassar. For academic purposes, the author can be contacted via e-mail at: rasbawecu@yahoo.comHow to cite this article? Asba, Abdul Rasyid. (2015). âMakassar Copra as a Trigger of Struggling for Power between Central and Local Government: A Historical Study of Regional Political Economy in Indonesiaâ in TAWARIKH: International Journal for Historical Studies, Vol.6(2) April, pp.197-212. Bandung, Indonesia: Minda Masagi Press and UNHAS Makassar, ISSN 2085-0980. Chronicle of the article: Accepted (February 27, 2015); Revised (March 27, 2015); and Published (April 28, 2015).